Adult-onset epilepsy and risk of traumatic brain injury: a nationwide cohort study - Posti Jussi P; Ruuskanen Jori O; Kytö Ville (BMJ PUBLISHING GROUP, 2025)
Background
A knowledge gap exists regarding the risk of traumatic brain injury (TBI) in patients with epilepsy.
Methods
Patients with adult-onset epilepsy during 2005-2018 in Finland were studied using retrospective longitudinal national registry-linkage design. Patients with epilepsy (n=35686; 51% men; mean age 56.6 years) were 1:1 matched to non-epileptic controls by age, sex, comorbidity burden and cohort entry year. The primary outcome was TBI leading to admission or death, secondary outcomes were TBI admission, fatal TBI, acute neurosurgical operations (ANOs) for TBI and TBI recurrence.
Results
The cumulative rate of the primary endpoint was 1.2% at 1 year, 5.6% at 10 years and 7.3% at 14 years in the epilepsy group versus 2.9% at 14 years in the matched controls (HR=3.77; p<0.0001). Epilepsy was associated with increased risk of TBI admission (6.9% vs 2.7%; HR=3.96; p<0.0001),ANOs (1.3% vs 0.4%; HR=7.00; p<0.0001) and fatal TBI (1.3% vs 0.5%; HR=3.82; p<0.0001), during follow-up. Competing risk analyses confirmed the association of epilepsy with all outcomes (p<0.0001). Epilepsy was associated with TBI recurrence during follow-up (HR 1.72; p=0.002).
Conclusion
Patients with adult-onset epilepsy have a significantly increased risk of severe and fatal TBI. The results underline the importance of TBI prevention in epilepsy.